2009
DOI: 10.1371/journal.pone.0004792
|View full text |Cite
|
Sign up to set email alerts
|

A Plant-Derived Recombinant Human Glucocerebrosidase Enzyme—A Preclinical and Phase I Investigation

Abstract: Gaucher disease is a progressive lysosomal storage disorder caused by the deficiency of glucocerebrosidase leading to the dysfunction in multiple organ systems. Intravenous enzyme replacement is the accepted standard of treatment. In the current report, we evaluate the safety and pharmacokinetics of a novel human recombinant glucocerebrosidase enzyme expressed in transformed plant cells (prGCD), administered to primates and human subjects. Short term (28 days) and long term (9 months) repeated injections with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(105 citation statements)
references
References 21 publications
0
101
0
4
Order By: Relevance
“…In pediatric patients, dose-normalized exposure indicated dose proportionality between 30 and 60 Units/kg. Previously, Aviezer et al [22] reported an earlier, Phase 1 study of the PK of taliglucerase alfa in healthy adult volunteers (n = 6) who received escalating doses administered intravenously at separate clinic visits (15 Units/kg on day 8, 30 Units/kg on day 15, and 60 Units/kg on day 22). Maximum plasma concentration of taliglucerase alfa was reached by approximately 80 min after the start of infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric patients, dose-normalized exposure indicated dose proportionality between 30 and 60 Units/kg. Previously, Aviezer et al [22] reported an earlier, Phase 1 study of the PK of taliglucerase alfa in healthy adult volunteers (n = 6) who received escalating doses administered intravenously at separate clinic visits (15 Units/kg on day 8, 30 Units/kg on day 15, and 60 Units/kg on day 22). Maximum plasma concentration of taliglucerase alfa was reached by approximately 80 min after the start of infusion.…”
Section: Discussionmentioning
confidence: 99%
“…12 Taliglucerase alfa (Protalix Biotherapeutics, Carmiel, Israel) is a carrot cell-expressed human recombinant ␤-glucocerebrosidase enzyme for IV treatment of Gaucher disease. 13 Expression of taliglucerase alfa is targeted in the plant cell to the storage vacuoles using a plant-specific C-terminal sorting signal that dictates the formation of the desired mannose structure in vivo, and unlike imiglucerase, does not require subsequent exposure of mannose residues in vitro. 14 Furthermore, taliglucerase alfa evinces biologic activity comparable with imiglucerase and its pharmacokinetic profile implies a prolonged half-life compared with imiglucerase, 13 although this is currently of unclear clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Initial reports 13,14 of the effects of treatment withdrawal in adult patients with stable disease suggest that, when appropriately monitored, some patients may safely interrupt treatment for a short period of time because irreversible complications are unlikely to occur in a couple of months. Alternatively, some patients have been switched to miglustat (the oral substrate reduction therapy) or to other ERTs -either velaglucerase alfa or taliglucerase alfa (developed by Protalix, which is produced in plant cells 15 ) -that have been made available through expanded access programmes. The collection of information on each patients' well being and their disease parameters following treatment switches is of utmost importance, which may be best achieved by creating an independent database of clinical assessments and standardized laboratory measurements, such as markers for Gaucher's storage cells 16,17 .…”
Section: Indicationsmentioning
confidence: 99%